Autoantibodies profile in patients with chronic hepatitis C and the influence of Interferon-alfa plus Ribavirin - Janaina LeitÃo Vilar (2006)
Chronic hepatitis C has been associated with non-organ-specific autoantibodies (NOSA) production. Despite of increasing number of researches about this subject, there is no agreement among the authors of which autoantibodies are produced during combinated therapy of interferon and ribavirin or the clinical relevance of NOSA in patientâs organism. Our aim was to evaluate the profile of NOSA in patients with chronic hepatitis C who attended to Walter CantÃdio Hospital (HUWC) and received combinated antiviral therapy (interferon-ribavirin). A total of 34 patients with hepatitis C were studied. Anti-nuclear antibody (ANA), anti-smooth muscle antibody (SMA), anti-liver/kidney microsomal antibody type 1 (LKM-1) and anti-mitochondrial antibody (AMA) were detected by indirect immunofluorescence. The presence of NOSA was related to clinical and epidemiological variables and to the outcome of antiviral combination therapy with interferon-alfa and ribavirin. Patients were classified as nonresponders, relapsers or long-term responders depending on the outcome of treatment. In our study, before therapy, 23 patients were NOSA positive (SMA was detected in 6 patients, SMA and AMA in 10 and SMA, AMA and ANA in 7). On the 24th week of treatment, 24 patientes were NOSA positive (SMA was detected in 4 patients, SMA and AMA in 10, ANA and SMA in 1, ANA and AMA in 1 and SMA, AMA and ANA in 8). NOSA behavior did not show significant variation during treatment. The overall rate of long-term response was 26,5% (9/34). Long-term response occurred in 17,4% (4/23) of NOSA positive patients and 45,5% (5/11) of NOSA negative patients. Positivity of autoantibodies was not associated with gender, age, viral genotype or aminotransferase levels. In conclusion, ANA was the only NOSA associated with treatment outcome. The absence of NOSA might indicate a significantly higher chance for viral clearance in response to combination therapy for chronic hepatitis C infection.